Fabrication of single-grain-layered garnet-type electrolyte sheets by a precursor method - Naoki Hamao; Koichi Hamamoto (Journal of Asian Ceramic Societies, 2022)
Thin and dense solid electrolytes are required to improve the performance of oxide-based all-solid-state batteries. We investigated the effect of the uniformity of dopant diffusion on the sinterability of the electrolyte, fabricated a garnet-type electrolyte sheet composed with a single grain along with thickness direction using the tape casting method. The electrolyte sheet using raw powder prepared by the precursor method exhibits a relatively high Li-ion conductivity of 6.7 × 10−4 S·cm−1 at 25°C and low activation energy of 0.33 eV. We then investigated the factors responsible for the densification of the obtained sheets by cross-sectional morphological observation and compositional analysis.